The potential of lactoferrin as antiviral and immune-modulating agent in viral infectious diseases - Eker, Furkan; Duman, Hatice; Ertürk, Melih; Karav, Sercan (Frontiers in Immunology, 2024)
Emerging infectious diseases are caused by unpredictable viruses with the dangerous potential to trigger global pandemics. These viruses typically initiate infection by utilizing the anionic structures of host cell surface receptors to gain entry. Lactoferrin (Lf) is a multifunctional glycoprotein with multiple properties such as antiviral, anti-inflammatory and antioxidant activities. Due to its cationic structure, Lf naturally interacts with certain host cell receptors, such as heparan sulfate proteoglycans, as well as viral particles and other receptors that are targeted by viruses. Therefore, Lf may interfere with virus-host cell interactions by acting as a receptor competitor for viruses. Herein we summarize studies in which this competition was investigated with SARS-CoV-2, Zika, Dengue, Hepatitis and Influenza viruses in vitro. These studies have demonstrated not only Lf’s competitive properties, but also its potential intracellular impact on host cells, such as enhancing cell survival and reducing infection efficiency by inhibiting certain viral enzymes. In addition, the immunomodulatory effect of Lf is highlighted, as it can influence the activity of specific immune cells and regulate cytokine release, thereby enhancing the host’s response to viral infections. Collectively, these properties promote the potential of Lf as a promising candidate for research in viral infectious diseases.